The partitioning technique of directed cyclic graph for task assignment problem - Ariffin, W. N. M. (American Institute of Physics Inc., 2016)
The scheduling and mapping of task graph to processors is considered to be the most crucial NP-complete in parallel and distributed computing systems. In this paper, the theoretical graph application using simple partitioning technique is presented to assign a number of tasks onto two processors. This paper addresses a directed-weighted cyclic graph. The effort is to reduce the graph onto directed acyclic graph. A Kernighan-Lin algorithm is applied to obtain the partition of tasks. Combining the technique of reduction and partitioning lead to an efficient graph-mapping concept.